Elaboration of a powdered anchovy protein hydrolyzate (Engraulis ringens) - Roldán A., David (2021)
The aim of this work was to obtain a protein powder hydrolyzate using headless and gutted anchovy (HG) and its sensory, physicochemical and microbiological characteristics were determined. In the hydrolysis process, seven commercial proteases were evaluated. The hydrolytic activity of the proteases was evaluated using the values of Brix degrees not corrected (°Bx ref.) and degree of hydrolysis). (GH %) The experimental procedure to obtain the powdered hydrolyzate was: reception of HG anchovy, washed, ground, weighed and mixed, addition of protease and water, hydrolyzed with stirring, filtered, centrifuged, dehydrated, packed and stored. The commercial proteases that presented the highest GH % over anchovy proteins were Protex 6L and Protamex with Flavourzyme 1000L. The doses of Protamex 0.2% and Flavourzyme 1000L of 0.4% respectively, in relation to the weight of the raw material, reached the highest values of °Bx ref. (11.50) and GH% (39.0%) at 2 hours of processing, The powdered anchovy protein hydrolyzate presented a powdery texture and soft to the touch, beige in color with light tones. The taste and smell were light of fish. Presented 77.13% of protein, 10.727 g of lysine / 100 of product and the low microbial load confirmed the adequate sanitary conditions in its elaboration.